Graphene field effect transistors with niobium contacts and asymmetric transfer characteristics. (4th November 2015) - Bartolomeo, Antonio Di; Giubileo, Filippo; Romeo, Francesco; Sabatino, Paolo; Carapella, Giovanni; Iemmo, Laura; Schroeder, Thomas; Lupina, Grzegorz
Abstract: We fabricate back-gated field effect transistors using niobium electrodes on mechanically exfoliated monolayer graphene and perform electrical characterization in the pressure range from atmospheric down to 10 −4 mbar. We study the effect of room temperature vacuum degassing and report asymmetric transfer characteristics with a resistance plateau in the n-branch. We show that weakly chemisorbed Nb acts as p-dopant on graphene and explain the transistor characteristics by Nb/graphene interaction with unpinned Fermi level at the interface.